Numerical and Experimental Investigations of a Double‐Suction Pump With a Middle Spacer and a Staggered Impeller - Wang, Zhe; Chen, Yongjun; Rakibuzzaman, Md; Agarwal, Ramesh; Zhou, Ling (Irrigation and drainage, 2025)
ABSTRACT Double‐suction pumps are among the most commonly used mechanical devices in irrigation and drainage. To investigate the effects of the impeller configuration with a spacer and staggered arrangement on the internal flow field and radial force characteristics of a double‐suction centrifugal pump, a comparison investigation was conducted using the same type of pump with three different impeller configurations: a symmetrically arranged impeller without a spacer, a symmetrically arranged impeller with a spacer and a staggered 25° arrangement impeller with a spacer. This study employed a combination of experimental and numerical simulation methods to analyse changes in the head, efficiency, transient radial force and internal flow field under three typical operating conditions. The results indicate that the staggered 25° arrangement impeller with a spacer results in a higher head and efficiency than both the symmetrically arranged impellers without a spacer and those with a spacer across most working conditions. Furthermore, the efficiency improvement is most significant at low flow rates for the staggered 25° arrangement impeller with a spacer compared with the other configurations. In terms of the internal flow field, the addition of a spacer and staggered 25° arrangement impeller effectively reduces the high‐velocity flow, making the pressure distribution gradient more reasonable and the turbulent kinetic energy distribution more uniform. Additionally, adding spacers and employing staggered arrangements effectively reduces the steady‐state radial forces as well as the main frequency amplitude of the radial force fluctuations on the impeller. This improves both the high‐velocity flow structure attenuation rate and outlet flow stability for double‐suction impellers. By comparing and analysing the external characteristics, internal flow field and radial force characteristics of different impeller configurations, this study proposes an improved impeller scheme based on a spacer and staggered arrangement, which provides a new optimization idea for improving the efficiency and stability of double‐suction centrifugal pumps in irrigation systems. Résumé Les pompes à double aspiration sont parmi les dispositifs mécaniques les plus couramment utilisés dans l'irrigation et le drainage. Pour étudier les effets de la configuration de la roue avec une entretoise et une disposition décalée sur le champ d'écoulement interne et les caractéristiques de la force radiale d'une pompe centrifuge à double aspiration, une enquête de comparaison a été effectuée en utilisant le même type de pompe avec trois configurations différentes de roue: une roue symétrique sans entretoise, une roue symétrique avec une entretoise et une roue décalée à 25° avec une entretoise. Cette étude a utilisé une combinaison de méthodes de simulation expérimentale et numérique pour analyser les changements survenus dans la charge, l'efficacité, la force radiale transitoire et le champ d'écoulement interne dans trois conditions de fonctionnement typiques. Les résultats indiquent que la roue à disposition décalée de 25° avec entretoise donne une charge et une efficacité plus élevées que les roues à disposition symétrique sans entretoise et celles avec entretoise dans la plupart des conditions de travail. En outre, l'amélioration du rendement est la plus significative à de faibles débits pour la roue à disposition décalée de 25° avec une entretoise par rapport aux autres configurations. En termes de champ d'écoulement interne, l'ajout d'une entretoise et d'une roue à disposition décalée de 25° réduit efficacement l'écoulement à grande vitesse, rendant le gradient de distribution de pression plus raisonnable et la distribution d'énergie cinétique turbulente plus uniforme. En outre, l'ajout d'entretoise et l'utilisation de disposition décalée réduit efficacement les forces radiales à l'état stationnaire ainsi que l'amplitude de fréquence principale des fluctuations de la force radiale sur la roue. Cela améliore à la fois le taux d'atténuation de la structure de l'écoulement à grande vitesse et la stabilité de l'écoulement de sortie pour les roues à double aspiration. En comparant et en analysant les caractéristiques externes, le champ d'écoulement interne et les caractéristiques de la force radiale de différentes configurations de roues, cette étude propose un schéma amélioré de roues basé sur une entretoise et une disposition décalée, qui fournit une nouvelle idée d'optimisation pour améliorer l'efficacité et la stabilité des pompes centrifuges à double aspiration dans les systèmes d'irrigation.